IMPACT OF CD44 EXPRESSION ON THE EFFECTIVENESS OF TREATMENT OF LOCALLY ADVANCED PRIMARY INOPERABLE BREAST CANCER PATIENTS - Smolanka, І.І.; Ivankova, V.S.; Ivankova, O.M. (World of Medicine and Biology, 2021)
The study included 157 breast cancer patients aged from 27 to 82 years with ІІIAІІІC stages of the disease, who had no positive response to 6 courses of anthracyclines and/or taxanes-based neo-adjuvant polychemotherapy (AC, FAC, AT). Main group included 74 patients who underwent a course of radiotherapy (RT) under radical program in traditional fractionation mode against the background of daily administration of the cytostatic fluoropyrimidine series drug. Tegafur was used at a dose of 750 mg/m2 daily throughout the radiotherapy course for the purpose of radiomodification. Сomparison group included 83 patients, who underwent radiotherapy alone in traditional fractionation mode. When using RT in conjunction with radiomodifier, we managed to achieve a better response to treatment in our study patients with CD44+ expression, namely to increase the number of partial response by 41.64 % (p=0,02), resectable cases by 17.28 % (p=0.016), to improve the grade of therapeutic pathomorphosis intensity, including through increasing the percentage of reaching pathomorphological complete response by 4.08 % (p=0.03), improving the overall 5-year survival rate by 28.51 % (p=0.01) and progressive-free survival rate by 37.72 % (p
Keywords: breast cancer; radiotherapy; fluoropyrimidine radioimodifier; CD44; tumor response; overall survival; recurrence-free survival